5΄-Vinylphosphonate improves tissue accumulation and efficacy of conjugated siRNAs in vivo. Issue 13 (7th June 2017) - Haraszti, Reka A.; Roux, Loic; Coles, Andrew H.; Turanov, Anton A.; Alterman, Julia F.; Echeverria, Dimas; Godinho, Bruno M.D.C.; Aronin, Neil; Khvorova, Anastasia
Abstract: 5΄-Vinylphosphonate modification of siRNAs protects them from phosphatases, and improves silencing activity. Here, we show that 5΄-vinylphosphonate confers novel properties to siRNAs. Specifically, 5΄-vinylphosphonate (i) increases siRNA accumulation in tissues, (ii) extends duration of silencing in multiple organs and (iii) protects siRNAs from 5΄-to-3΄ exonucleases. Delivery of conjugated siRNAs requires extensive chemical modifications to achieve stability in vivo . Because chemically modified siRNAs are poor substrates for phosphorylation by kinases, and 5΄-phosphate is required for loading into RNA-induced silencing complex, the synthetic addition of a 5΄-phosphate on a fully modified siRNA guide strand is expected to be beneficial. Here, we show that synthetic phosphorylation of fully modified cholesterol-conjugated siRNAs increases their potency and efficacy in vitro, but when delivered systemically to mice, the 5΄-phosphate is removed within 2 hours. The 5΄-phosphate mimic 5΄-( E )-vinylphosphonate stabilizes the 5΄ end of the guide strand by protecting it from phosphatases and 5΄-to-3΄ exonucleases. The improved stability increases guide strand accumulation and retention in tissues, which significantly enhances the efficacy of cholesterol-conjugated siRNAs and the duration of silencing in vivo . Moreover, we show that 5΄-( E )-vinylphosphonate stabilizes 5΄ phosphate, thereby enabling systemic delivery to and silencing in kidney and heart.